Wireless Connectivity Based-IoT for Water Monitoring System in Comet Goldfish - Amri, Muhammad Izwan; Basir, Budiman Azzali (Evolution in Electrical and Electronic Engineering, 2024)
The goal of a red white comet fishpond water monitoring system is to provide real-time monitoring and control of water quality parameters. Being a very adaptive freshwater fish, comet goldfish needs water conditions for optimum development and health. The water monitoring system allows fish producers to closely monitor and control important variables including temperature, turbidity, and pH. To measure these factors, the system uses a variety of sensors, including temperature, pH, and turbidity sensors. To ensure precise and dependable data collection, these sensors are placed in the water body strategically. A microcontroller, such as an ESP32, which serves as the system's central processing unit, processes and analyses the sensor which the aquarist can remotely access and view the current water quality data by using a monitoring station or cloud-based platform to receive wireless transmission of the collected data. This makes it possible for them to spot any deviations or anomalies in the water parameters and take the necessary action, such modifying the feeding schedule, managing aeration, or starting water exchange to maintain the condition of the water.